AGE AND GROWTH OF THE SCAD DECAPTERUS DAYI WAKIYA - Sreenivasan, P V (Indian Journal of Fisheries, 2011)
Decapteiiix dayi Wakiya attains a length of 150 mm in the first year and184 mm by 19 months at Vizhinjam. Maximum growth of 30 mm and 20 mm wasnoticed during the first and second months, respectively. Though many broodsenter into the fishery in the same year, those bom in April manifest strongly inthe fishery than the earlier and later ones. The younger broods tend to catch upthe older ones by faster growth and form a unimodal group at the size of 120-129mm, and are found as a distinct unimodal size class then onwards